No effect of cycling shoe sole stiffness on sprint performance. (2nd January 2021) - Hurt, James W.; Kram, Rodger
Abstract: Most competitive and recreational road cyclists use stiff-soled shoes designed for cycling and 'clipless' pedals that firmly attach to the shoes. There are many unsubstantiated claims by cyclists and industry professionals about the advantages of cycling shoes and clipless pedals. Scientific research has shown that cycling shoes and clipless pedals have no significant effects on the metabolic cost of cycling during submaximal, steady-state efforts. However, a recent study demonstrated that, compared to running shoes, cycling shoes and clipless pedals do provide performance benefits relevant to sprint cycling. Here, we investigated if there was a positive relationship between longitudinal bending stiffness of cycling shoe soles and sprint performance. We measured the mechanical power outputs, velocities, and cadences of 19 healthy male recreational/competitive cyclists during maximal sprint cycling. All participants rode outdoors on a paved asphalt road with a steady, uphill grade of 4.9%. Each subject completed a total of nine 50 m cycling sprints in three (single-blinded) shoe conditions (each condition was replicated three times): identical shoe uppers with injection moulded nylon soles, carbon fibre-fibreglass blend soles, and full carbon fibre soles. The same clipless pedals were used throughout all tests. No significant differences were detected between the three shoe soles for: 50 m average and peak 1-second power, average change and peak change in velocity, average and peak cadence, maximal sprint velocity, peak acceleration, and peak crank torque (all p > 0.31). Greater longitudinal bending stiffness of cycling shoe soles had no effect on sprint performance during short uphill sprints.